2018
DOI: 10.1039/c7cy01753g
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and catalytic performance of MOF-derived Fe@C/Al composites for high temperature Fischer–Tropsch synthesis

Abstract: The synthesis of MOF/AlOOH derived composites enhances the selectivity towards light olefins in HTFTS and the mechanical stability of the catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…For more efficient production of high value-added hydrocarbons in HT-FTS, active and thermally stable nanocatalysts such as Fe@C core-shells and Fe@graphene with high Fe load (> 20wt%) and small particle sizes (< 20 nm) have been developed [30][31][32][33]. The catalysts, which have active Fe sites greatly exposed in the FTS reaction, have demonstrated increased productivity of valuable hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…For more efficient production of high value-added hydrocarbons in HT-FTS, active and thermally stable nanocatalysts such as Fe@C core-shells and Fe@graphene with high Fe load (> 20wt%) and small particle sizes (< 20 nm) have been developed [30][31][32][33]. The catalysts, which have active Fe sites greatly exposed in the FTS reaction, have demonstrated increased productivity of valuable hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Fe-MOF derived Fe@C catalysts demonstrated high activity and stability in FTS. 189,[191][192][193] The obtained MOFs derived Fe@C catalysts showed a high iron dispersion and extremely small Fe nanoparticles confined within a porous carbon matrix.…”
Section: Mof-derived Iron Catalystsmentioning
confidence: 95%
“…Inspired by the Fe/g-Al 2 O 3 catalysts, with strong mechanical strength, they also prepared MOF-derived iron-based catalyst with enhanced dispersion of the active phase and excellent mechanical strength for producing lower olefins from HTFT. 193 The Fe@C/Al catalyst was obtained by wet extrusion of different amounts of Basolite F300 and AlOOH followed by subsequent pyrolysis, which showed enhanced C 2 -C 4 selectivity and mechanical stability. There are various MOF derived carbonaceous materials, such as nanoporous hybrid carbon being worthy of further study.…”
Section: Mof-derived Iron Catalystsmentioning
confidence: 99%
“…Interestingly, the incorporation of AlOOH to iron-BTC followed by pyrolysis at 500 °C under nitrogen atmosphere gave rise to composites of mesoporous structures, a high Fe/Fe 3 O 4 ratio, the average particle size of 10-35 nm and coordinatively unsaturated Al 3 + sites. Finally, it is crystal clear from the above studies that MOFMS is an effective strategy to prepare highly dispersed Fe-based with high loading catalysts https://engine.scichina.com/doi/10.1016/j.jechem.2020.03.062 from parent MOFs with good textural properties and outstanding FTS catalytic performances [76] . The summary of Fe-MOF precursors, Fe wt%, and other textural Properties of the MOF-derived Fe FTS catalysts obtained via MOFMS are given in Table 1 .…”
Section: Fe-fts Catalysts From Mofmentioning
confidence: 98%
“…Similarly, Gascon et al the FT performance of Fe@C/Al fabricated from Fe-BTC MOF and AlOOH binder was tested in HTFS at 340 °C, 15 bar, H 2 /CO = 1, GHSV = 55 mmol CO,STP g Fe −1 min −1 [76] . It was observed that Fe@C/Al catalyst exhibited excellent mechanical resistance during FT operation, hence, enhancing C 2 -C 4 selectivity and mechanical stability of the iron catalyst, but the activity decreases with an increase in aluminum content.…”
Section: Mof-derived Fe-based Catalystsmentioning
confidence: 99%